2017
DOI: 10.1007/s10479-017-2426-2
|View full text |Cite
|
Sign up to set email alerts
|

Giving voice to the silent: a framework for understanding stakeholders’ participation in socially-oriented initiatives, community-based actions and humanitarian operations projects

Abstract: Under the umbrella of compassionate operations management theory (Sarkis, in Int J Prod Econ 139(2): [359][360][361][362][363][364][365] 2012) and stakeholder theory, the aim of this article is to propose a comprehensive framework to unlock stakeholders' voice in socially-oriented projects (for example, social responsibility, community and humanitarian projects). The framework developed in this work aims to assist managers to measure the level of engagement of stakeholders during socially-oriented projects' e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
0
23
0
3
Order By: Relevance
“…We also used plots of residuals by predicted values, rankits plot of residuals, and statistics of skewness and kurtosis (Cohen et al 2003). We found that the indicators for skewness and kurtosis are much lower than the specified limits in past research (Curran et al 1996;Kim and Malhotra 2005;Dubey and Gunasekaran 2015). Hence, we did not observe any significant deviations from the normality assumption.…”
Section: Data Analyses and Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We also used plots of residuals by predicted values, rankits plot of residuals, and statistics of skewness and kurtosis (Cohen et al 2003). We found that the indicators for skewness and kurtosis are much lower than the specified limits in past research (Curran et al 1996;Kim and Malhotra 2005;Dubey and Gunasekaran 2015). Hence, we did not observe any significant deviations from the normality assumption.…”
Section: Data Analyses and Resultsmentioning
confidence: 87%
“…While the direct impact of natural disasters on human life and property could be reduced by proper investment in mitigation and preparedness, the effectiveness of post-disaster relief to survivors can be undermined by poor management (Özdamar et al 2004;Altay 2008;Coles et al 2017;de Camargo et al 2017). Suffering of the affected population may be prolonged due to lack of coordination among humanitarian actors responding to the event (Jin et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…de Camargo et al 2017;DuHadway et al 2017;Fosso Wamba et al 2017;Sushil (2017a,b) Quantitative ( 45)…”
Section: Future Research Directionsunclassified
“…right goods or service, right place, right time, and right condition) are critical factors of success. However unlike commercial supply chains, disaster relief teams typically do not have all the necessary information to ensure the humanitarian supply chain works effectively and efficiently, such as knowledge of the needs of survivors or useful alternative routes to administer aid in disaster-hit locations (Seybolt 2009 ; Swanson and Smith 2013 ; Behl and Dutta 2019 ; Gupta et al 2019 ; De Camargo et al 2019 ; Ivanov and Dolgui 2020 ).…”
Section: Introductionmentioning
confidence: 99%